Antimesenteric sleeve tapering enteroplasty with end-to-end anastomosis versus primary end-to-side anastomosis for the management of jejunal/ileal atresia - Mazen Kurdi; Ahmed Mokhtar; Mahoud Elkholy; Heidi El-wassia; Maha Bamehriz; Aya Kurdi; Mohammad Khirallah (Asian Journal of Surgery, 2023)
Background/objective: Small bowel atresia commonly causes neonatal intestinal obstructions. Technical problems are associated with the surgical management of atresia using primary end–to–end anastomosis. Furthermore, the significantly dilated proximal loop may be associated with the stasis of intestinal fluid, thus increasing pressure on the anastomosis and prolonging fasting time before initiation of oral intake. This study aimed to perform antimesenteric tapering of the proximal loop using a linear stapler to reduce its diameter and facilitate anastomosis with the distal loop. Methods: This retrospective study included 57 neonates diagnosed with jejunoileal atresia. They were categorised into two groups: Group A (n = 29), which included neonates treated using antimesenteric sleeve enteroplasty tapering using a linear stapler and Group B (n = 28), which included neonates treated at the primary end of the proximal loop to the side of the distal loop anastomosis. Results: The mean operative time was 122.5 min in group A vs. 118 min in group B, and the mean duration to reach full oral intake was 17 days in group A vs. 20.2 days in group B (p = 0.03). The mean length of hospital stay was 25 and 35 days in groups A and B, respectively (p = 0.042). Conclusion: Tapering the proximal dilated bowel loop to achieve anastomosis with the distal loop improved the transient time, reduced stasis and its associated translocation and colonisation, and allowed for early initiation and maintenance of oral intake. All these parameters shortened the overall length of hospital stay.